Achalasia cardia causing left atrial compression diagnosed on echocardiography - Dev, Munish; Patel, Tejas M.; Shah, Sanjay C.; Tiwari, Pradyot; Sharma, Madhurima (Indian Journal of Case Reports, 2019)
-